Inclusive Models for Developing Entrepreneurship Education at Islamic Boarding Schools: A Case Study of Pondok Pesantren Orang Bertaqwa Temanggung - Pradewi, Gunarti Ika; Kurniandini, Sholeh; Hazam, Alwi Gusmam Nur; Heni, Naskhul (Muallimun : Jurnal Kajian Pendidikan dan Keguruan, 2025)
This study examines the potential for developing an inclusive entrepreneurship education model in Indonesian Islamic boarding schools (pondok pesantren), a context often characterized by closed and selective educational practices. Using a qualitative descriptive approach, data were collected through in-depth interviews with eight key informants, observations, and document analysis at Pondok Pesantren Orang Bertaqwa, Temanggung. The findings indicate that pesantren-based business units function as effective entrepreneurship laboratories and support students’ daily needs. However, access to entrepreneurial activities remains limited to selected students, resulting in unequal learning opportunities. At the same time, the openness of pesantren business units to community collaboration highlights their potential role in local economic empowerment. These findings underscore the need for a more inclusive and participatory entrepreneurship education model that ensures broader student involvement while maintaining pesantren values. This study contributes to entrepreneurship education theory by proposing an inclusive model tailored to Islamic boarding schools and offers practical implications for policymakers and practitioners seeking to strengthen the social and economic functions of pesantren through sustainable and equitable entrepreneurship education.